PERAN TEKANAN TEMAN SEBAYA DALAM MEMPREDIKSI PERILAKU BULLYING PADA REMAJA - Huriati, Huriati; Arbianingsih, Arbianingsih; Mukhtar, Musdalifah; Hadrayani, Eka; Asyifa, Nur; Binti Ismail , Siti Nooraini (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Background: Bullying among adolescents is a pressing global issue with significant psychosocial consequences. Peer pressure plays a complex role as both a direct and indirect facilitator of bullying behaviour, alongside other factors that warrant further exploration. Objective: This study aimed to examine the relationship between peer pressure and bullying behaviour among adolescents. Method: A quantitative cross-sectional survey was conducted with 274 students aged 12–15 years, selected through random sampling. Data were collected using two validated instruments: the Revised Olweus Bullying/Victim Questionnaire (23 items) and the Peer Pressure Questionnaire (25 items). Data were analysed using Spearman’s rank correlation to assess the association between variables. Result: Findings showed that 60.2% of participants exhibited high levels of bullying behaviour, with verbal and non-physical bullying being the most prevalent types. A significant positive correlation was found between peer pressure and bullying behaviour (r = 0.583; p < 0.001), indicating that higher peer pressure is associated with increased bullying among adolescents. Conclusion: Peer pressure plays a crucial role in shaping adolescent bullying behaviour. These findings highlight the importance of peer-based interventions and supportive school environments in preventing bullying.